On some problems of variable population poverty comparisons - Nicole Hassoun; S. Subramanian (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper demonstrates that the property of 'replication invariance', generally considered to be an innocuous requirement for the extension of fixed-population poverty comparisons to variable-population contexts, is incompatible with other plausible variable- and fixed-population axioms.
Keywords: I32; D63; D30; 330; variable populations; fixed populations; replication invariance; population focus; income focus; impossibility result